2016
DOI: 10.1021/acsnano.6b04028
|View full text |Cite
|
Sign up to set email alerts
|

Threading through Macrocycles Enhances the Performance of Carbon Nanotubes as Polymer Fillers

Abstract: In this work, we study the reinforcement of polymers by mechanically interlocked derivatives of single-walled carbon nanotubes (SWNTs). We compare the mechanical properties of fibers made of polymers and of composites with pristine SWNTs, mechanically interlocked derivatives of SWNTs (MINTs), and the corresponding supramolecular models. Improvements of both Young’s modulus and tensile strength of up to 200% were observed for the polystyrene–MINT samples with an optimized loading of just 0.01 wt %, while the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…Our results illustrate how the combination of covalent and noncovalent chemistries opens the door to novel types of functionalization of SWNTs in which the degree of functionalization, the electronic interaction between the nanotubes and their supramolecular partners, and, most remarkably, their topology 51 can be varied.…”
Section: Discussionmentioning
confidence: 86%
“…Our results illustrate how the combination of covalent and noncovalent chemistries opens the door to novel types of functionalization of SWNTs in which the degree of functionalization, the electronic interaction between the nanotubes and their supramolecular partners, and, most remarkably, their topology 51 can be varied.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, 1 H NMR (400 MHz) experiments confirmed the disappearance of the alkene signals, and the appearance of signals at 4.61 and 4.40 ppm, that can be attributed to the new aliphatic protons. Moreover, all signals appear broadened, which is characteristic of the formation of high‐molecular weight species (see Figure S16) …”
Section: Resultsmentioning
confidence: 99%
“…In collaboration with Dario Pisignano and Juan J. Vilatela, we have recently shown that the encapsulationo fS WNTst of orm MINTsr esultsi ns ignificant improvements in the reinforcement of electrospun polystyrene (PS) fibers. [70] In fact, the Young's moduli and tensile strength were enhanced up to 200 %i nt he PS-MINTs amples, withj ust 0.01 wt %o fM INTs. More importantly,supramolecular modelswith identicalchemical composition and loading had no effect, or even weakenedt he final fibers.…”
Section: Possible Applications Of Mints: Polymer Fillers Catalysis mentioning
confidence: 96%